A Study of Combinations of Factors in the Marketization of Open Data of Local Governments in China on the Perspective of the Configurations - Lili Wei; Bin Gu (Discrete Dynamics in Nature and Society)
The Chinese Government and Statistics Departments have collected huge amounts of data. They use these government open data to conduct applied research and technological studies, including the establishment of a market-based system for data elements. These data are put into e-government to build the construction of digital government and improve the level of government services continuously. This paper uses the perspective of the configurations to discuss the combinations of factors in the marketization of open data of local governments in China with fsQCA method; this paper is based on the TOE framework, and the indices of the data layer of the government open data forest in 16 provinces are taken as the research object. The conclusions are as follows: (1) the market-oriented utilization paths of local government open data are categorized as technology-led, management-resource-led, economic and technology-driven, and location-advantaged. (2) Under certain conditions, when the number of data developers is small, and there is no dedicated government data management agency, optimizing and improving the government open data platform could be an alternative path to promote the effective use of local government open data in the market.